Weak association between arterial hypertension and overactive bladder baseline symptoms and treatment responses - Michel, Martin C.; Heemann, Uwe; de la Rosette, Jean J. M. C. H. (Frontiers in Pharmacology, 2022)
While animal studies have suggested an association between the presence of hypertension and the presence and/or severity of overactive bladder syndrome (OAB) symptoms, little clinical data is available. We have conducted a pre-specified secondary analysis of a non-interventional study involving 4450 OAB patients being treated with solifenacin to explore the existence of an association between OAB and hypertension using three parallel and overlapping definitions of hypertension to enhance robustness of analysis. Regardless of definition, patients with hypertension were older and had greater OAB symptom severity in univariate analyses. In multiple regression models including age as explanatory covariate, most relationships held up but effect sizes of concomitant hypertension on OAB severity were small (odds ratios <1.35 in all cases) and were deemed to be unlikely of clinical relevance. % Changes in symptom severity were somewhat smaller in univariate analysis, but effect sizes were small. We conclude that OAB and arterial hypertension are associated but effect sizes are too small to justify adaptation of clinical practice for OAB patients with concomitant hypertension.